Changes in basophil reactivity and synthesis of specific immunoglobulins E influenced by allergen-immunotherapy - L. Yu. Barycheva; L. V. Dushina; Yu. N. Medvedenko (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
The study focused on spontaneous and allergen-induced basophil activation (BAT) as well as on specific IgE indicators to major meadow grass pollen allergens on the background of allergen-immunotherapy (AIT) in patients sensitized to weed pollen. The study revealed that the specific IgE indicators to major ragweed allergens (nAmb a 1) and wormwood (nArt v 1) allergens, as well as the ratios of spec. IgE nAmb a 1/gen. IgE, and spec. IgE nArt v 1/gen. IgE do not change after 2 courses of pre-seasonal ASIT. There was a decrease detected in BAT indicators under the effect of ASIT. An early decrease in the BAT stimulation index (BAT IC) was shown to be more common for patients with positive treatment outcomes.